Wild animal trade in Cameroon: An insight into species involved and conservation implications in the western Highlands - Majiteu, Murielle; Tamungang, Simon Awafor; Fotang, Chefor; Tache, Jose Innoncent Tamdjo; Riegert, Jan (Ecological solutions and evidence, 2024)
Illegal bushmeat trade is a significant driver of the decline in wildlife populations within the tropics. Despite the intense trade of bushmeat in Cameroon, there is dearth or no official statistics on the kind of animals sold in the markets in most parts of Cameroon. To abridge this knowledge gap, an inventory of wild animals sold in local markets was carried out. The animal taxa sold within the markets were identified, and their abundance, class diversity and conservation status according to the IUCN Red List of threatened species and Cameroon wildlife classification were assessed. Semi‐structured questionnaires were randomly administered to 200 traders randomly selected in 16 markets. Multivariate analyses were used to compare the proportions of sold taxa among the markets and the proportions of taxa based on their conservation status. Results were summarized as shown below: (1) 476 individuals of animals were recorded, covering 47 taxa, 41 genera, 33 families, 18 orders and 3 classes from bushmeat vendors. (2) Mammals dominated the trade in all markets (by a mean of 74.3% per market), followed by reptiles (16.1%) and birds (9.5%) in terms of both abundance and diversity. (3) Cane rats (Thryonomyidae) and primates (Cercopithecidae) represented the highest proportions of animal specimens recorded. (4) The diversity of mammals sold was highest in Foumbot, followed by Bangangte, Bafousam and Bangoua as the main local markets, and lowest mammalian diversity was found in Batcham and Baham village markets. (5) The most often traded animal species belonged to the least concern category, followed by vulnerable, near threatened, endangered, and critically endangered. In general, we observed that less protected species by the IUCN Red List and Cameroon wildlife classification were often found in village markets and species with higher conservation value were often sold in city markets. Similarly, the main markets hosted the highest diversity of sold animals, especially mammals. The size of the human settlement together with its location nearby protected area and/or placement of the market by the main road are the main drivers determining numbers and diversity of sold animals, and further attention to government conservation activities should be focused on these markets. The size of the human settlement together with its location nearby protected area and/or placement of the market by the main road are the main drivers determining numbers and diversity of sold animals, and further attention to government conservation activities should be focused on these markets.